Ultracompact Silicon-On-Insulator Couplers for Multicore Fibers - Pita Ruiz, Julián L.; Rocha, Lucas G.; Yang, Jun; Kocabaş, Şükrü Ekin; Li, Ming-Jun; Aldaya, Ivan; Ménard, Michaël; Dainese, Paulo; Gabrielli, Lucas H. (American Chemical Society (ACS), 2022)
Fiber-to-chip couplers are critical devices to support interconnections between fibers and photonic integrated circuits. The advent of spatial division multiplexing (SDM) systems based on multicore fibers makes these devices subject to increasingly demanding footprint and coupling requirements. In addition to size and efficiency requirements, the manufacturing constraints and large parameter space result in a challenging optimization problem. This article applies topology optimization to design three integrated couplers for multicore fibers with an intercore spacing of 32 μm. By individually optimizing the radiating and tapering regions, we design and experimentally demonstrate two devices: the first with perpendicular coupling and an efficiency of -3.8 dB, with a footprint of 15 μm × 10 μm, and the second with a 10° coupling angle and an efficiency of -2.9 dB, with a footprint of 20 μm × 10 μm. Furthermore, by applying topology optimization over the whole design region, we improved the simulated efficiency to -1.9 dB within a footprint of only 10 μm × 10 μm, which represent the most compact CMOS-compatible coupler to date with efficiency among the highest in class. These are the first devices that can enable direct coupling between silicon chips and multicore fibers with intercore separation below 25 μm.
Keywords: integrated photonics; multicore fibers; photonic interconnects; silicon photonics; topological optimization